2004
DOI: 10.3748/wjg.v10.i23.3506
|View full text |Cite
|
Sign up to set email alerts
|

HDR-192Ir intraluminal brachytherapy in treatment of malignant obstructive jaundice

Abstract: AIM:To determine the feasibility and safety of intraluminal brachytherapy in treatment of malignant obstructive jaundice (MOJ) and to evaluate the clinical effect of intraluminal brachytherapy on stent patency and patient survival. METHODS:Thirty-four patients with MOJ were included in this study. Having biliary stent placed, all patients were classified into intraluminal brachytherapy group (group A, n = 14) and control group (group B, n = 20) according to their own choice. Intraluminal brachytherapy regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The MOS of 17.5 and 16 months achieved in group 1 and 2 respectively was similar to the studies delivering similar doses of radiation. EBBT alone is also shown to prolong the stent patency rate (17). In practice, several patients may fail to be subsequently fit for EBRT or palliative chemotherapy after biliary stenting.…”
Section: Discussionmentioning
confidence: 99%
“…The MOS of 17.5 and 16 months achieved in group 1 and 2 respectively was similar to the studies delivering similar doses of radiation. EBBT alone is also shown to prolong the stent patency rate (17). In practice, several patients may fail to be subsequently fit for EBRT or palliative chemotherapy after biliary stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective series have shown a progression-free and overall survival benefit with the addition of brachytherapy to EBRT (13)(14)(15)(16)(17). One of the proposed mechanisms in these small studies was felt to be secondary to increasing longevity of stent patency (17,24). Stent patency can also enhance patients' tolerability to chemotherapy by decreasing bilirubin levels (25).…”
Section: Discussionmentioning
confidence: 99%
“…The iridium-192 strands are intraluminally placed at the site of the tumor or stricture through PTBD catheter. Chen et al [59] , found 98% success rate of intraluminal brachytherapy using Iridium-192 in 34 patients of malignant biliary obstruction and concluded that intraluminal brachytherapy is a safe palliative therapy and improves patient survival. In photodynamic therapy, a photosensitizer is injected intravenously followed by application of light to the tumor, endoscopically or through PTBD route.…”
Section: Intra-biliary Palliative Therapymentioning
confidence: 99%